College Expansion and Curriculum Choice - Michael Kaganovich; Xuejuan Su (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper analyzes the impact of college enrollment expansion on student academic achievements and labor market outcomes in the context of competition among colleges. When public policies promote “access” to college education, colleges adjust their curricula: Less selective public colleges adopt a less demanding curriculum in order to accommodate the influx of less able students. As we argue in the paper, this adjustment benefits low-ability college students at the expense of those of medium ability. At the same time, this reduces the competitive pressure faced by elite colleges, as less selective colleges become a less appealing alternative for the medium ability students. The selective, elite colleges therefore adopt a more demanding curriculum to better serve their most able students, again at the expense of medium ability students. The model offers an explanation to two sets of empirical phenomena: (i) the observed U-shaped earnings growth profile among college-educated workers in the U.S. and (ii) the diverging selectivity trends of American colleges.
Keywords: I21; I23; I24; J24; H44; 330; curriculum; postsecondary education; enrollment expansion; income distribution